Volume 5: Turbo Expo 2002, Parts a and B 2002
DOI: 10.1115/gt2002-30641
|View full text |Cite
|
Sign up to set email alerts
|

Application of Casing Circumferential Grooves for Improved Stall Margin in a Transonic Axial Compressor

Abstract: Experimental and numerical investigations were conducted to study the fundamental flow mechanisms of circumferential grooves in the casing of a transonic compressor and their influence on compressor stall margin. Three different groove configurations were tested in a highly loaded transonic compressor. Experimental results show that circumferential grooves increase the stall margin of the compressor at the tested operating condition. Grooves with a much smaller depth than conventional designs are shown to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 0 publications
1
52
0
1
Order By: Relevance
“…So it is a goal to maintain the positive effects (increased surge pressure ratio in combination with high efficiency) while at the same time reducing the geometric volume of the device. On this regard, an experimental and numerical investigation on the first rotor of a two-stage compressor showed that grooves with a much smaller depth than conventional designs are similarly effective in increasing the stall margin (Rabe & Hah, 2002). The same work also showed that two shallow grooves placed near the leading edge are better than five deep or shallow grooves all over the blade tip.…”
Section: Circumferential Groove-type Treatmentsmentioning
confidence: 67%
“…So it is a goal to maintain the positive effects (increased surge pressure ratio in combination with high efficiency) while at the same time reducing the geometric volume of the device. On this regard, an experimental and numerical investigation on the first rotor of a two-stage compressor showed that grooves with a much smaller depth than conventional designs are similarly effective in increasing the stall margin (Rabe & Hah, 2002). The same work also showed that two shallow grooves placed near the leading edge are better than five deep or shallow grooves all over the blade tip.…”
Section: Circumferential Groove-type Treatmentsmentioning
confidence: 67%
“…In the following section, three recent studies that combine both experimental and numerical methods are reviewed. Rabe and Hah [2002] studied effects of circumferential grooves on a two-stage transonic axial compressor. Detailed numerical study was conducted to investigate flow mechanism of circumferential grooves.…”
Section: Previous Experimental and Numerical Investigations On Circummentioning
confidence: 99%
“…Paulon and Dehoudt [1982] conducted a theoretical investigation of the effects of circumferential grooves. Rabe and Hah [2002] investigated circumferential grooves applied to the first stage rotor in a modern highly loaded two-stage transonic axial compressor. They found that the local flow incidence near the pressure side of the leading edge is reduced due to the circumferential grooves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps one of the most successful techniques alleviating the stall/surge phenomena is the different configuration of casing treatment means such as slots or grooves over a rotor blade tip [1][2][3][4]. Unfortunately, most of the suggested and investigated casing treatment configurations cause a significant drop in efficiency.…”
Section: Introductionmentioning
confidence: 99%